Impact of root exudates on soil reconstruction and bacterial community resumption in open-pit coal mines - Yang, Zhuo; Niu, Jianzhi; Wu, Tong; Li, Jiaqi; Zhang, Linus; Chen, Xiongwen; Berndtsson, Ronny (Frontiers in Microbiology, 2025)
Open-pit coal mine reconstructed ecosystems are ecologically fragile. Retained early stage topsoil is usually not enough to maintain plant growth. For this purpose, we used root exudates to fertilize the reconstructed soil and improve the functioning of the soil microorganism ecology. The roots’ exudates increased the concentration of organic matter and total nitrogen by 16–39%. Within a certain concentration range, the higher the concentration of root exudate, the higher the soil fertility. When the concentration of root exudate was 85%, the bacterial abundance decreased. The soil inorganic nitrogen N-NH4+ and N-NO3− increased significantly by 11–21%. This significantly improved root growth and plant biomass for the reconstructed soil. The dominating bacterial community was driven by both root exudate components and plant root growth. Especially, the abundance of soil bacteria Actinobacteriota, Proteobacteria, and Chloroflexi was significantly promoted. Consequently, root exudates can be used to efficiently increase the soil fertility and improve the function and vegetation restoration in the soil reconstruction of mines.